PENGARUH PEMANFAATAN SISTEM OPAC (ONLINE PUBLIC ACCESS CATALOGUE) TERHADAP EFEKTIVITAS LAYANAN KOLEKSI DI PERPUSTAKAAN DAERAH PURWAKARTA - Hakim, Renaldi; Muhamad Taufik Bintang Kejora; Muchdjabir Wahid (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the use of the OPAC (Online Public Access Catalogue) system, determine the condition of collection services, and analyze the influence of the OPAC system on the effectiveness of collection services in the Purwakarta Regency Regional Library. This study uses a quantitative approach with a survey method. Data was obtained through the distribution of questionnaires to selected library users using random sampling techniques. The research analysis focused on the relationship between the utilization of the OPAC system and the effectiveness of library collection services. The results of the study show that the OPAC system has an important role in supporting the ease of access to information, the speed of collection search, and the accuracy of information retrieval for users. However, the use of OPAC in the Purwakarta Regency Regional Library is not fully optimal because there are still many users who depend on the assistance of librarians and the limited use of OPAC facilities. Therefore, optimizing the use of OPAC is needed to increase the effectiveness of collection services and the quality of information technology-based library services.